Impact of standardization on racial and socioeconomic disparities in non-accidental trauma evaluations in infants in a pediatric emergency department - Laura Even Elliott; Michael A. Gittelman; Eileen M. Kurowski; Elena M. Duma; Wendy J. Pomerantz (BMC, 2023)
Abstract Background Studies have illustrated racial and socioeconomic disparities in evaluation of non-accidental trauma (NAT). We aimed to investigate how implementation of a standardized NAT guideline in a pediatric emergency department (PED) impacted racial and socioeconomic disparities in NAT evaluation. Results 1199 patients (541 pre- and 658 post-guideline) were included for analysis. Pre-guideline, patients with governmental insurance were more likely than those with commercial insurance to have a social work (SW) consult completed (57.4% vs. 34.7%, p < 0.001) and a Child Protective Services (CPS) report filed (33.4% vs. 13.8%, p < 0.001). Post-guideline, these disparities were still present. There were no differences in race, ethnicity, insurance type, or social deprivation index (SDI) in rates of complete NAT evaluations pre- or post-guideline implementation. Overall adherence to all guideline elements increased from 19.0% before guideline implementation to 53.2% after (p < 0.001). Conclusion Implementation of a standardized NAT guideline led to significant increase in complete NAT evaluations. Guideline implementation was not associated with elimination of pre-existing disparities in SW consults or CPS reporting between insurance groups.